1995
DOI: 10.1159/000176909
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Function during Brain Natriuretic Peptide Infusion in Man

Abstract: To investigate the cardiovascular effects of pathophysiological levels of brain natriuretic peptide (BNP), 7 healthy subjects were submitted to equilibrium radionuclide angiocardiography in baseline conditions and during BNP infusion at increasing doses (4, 8, 10 and 12 pmol/kg·min for 20 min each). BNP induced a progressive, significant reduction in left ventricular end diastolic volume, stroke volume and end systolic volume and an increase in ejection fraction and heart rate. Cardiac output, arterial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…In fact, changes in preload as well as in inotropism might compensate for the reduction in afterload induced by vasodilation, 40 resulting in the maintenance of CO and arterial pressure. Indeed, such a phenomenon has been observed by our group in healthy subjects 26 and patients with essential hypertension 27 receiving low-dose BNP. In fact, BNP significantly reduced LV EDVI and stroke volume, whereas CO did not decline, due to compensatory increases in HR and in LV emptying, as indicated by increments in ejection fraction and reductions in ESVI.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In fact, changes in preload as well as in inotropism might compensate for the reduction in afterload induced by vasodilation, 40 resulting in the maintenance of CO and arterial pressure. Indeed, such a phenomenon has been observed by our group in healthy subjects 26 and patients with essential hypertension 27 receiving low-dose BNP. In fact, BNP significantly reduced LV EDVI and stroke volume, whereas CO did not decline, due to compensatory increases in HR and in LV emptying, as indicated by increments in ejection fraction and reductions in ESVI.…”
Section: Discussionsupporting
confidence: 56%
“…25 We recently showed that intravenous infusion of low-dose BNP markedly affects cardiac function in the absence of any appreciable changes in CO and peripheral vascular resistance. 26,27 These considerations prompted us to evaluate cardiac volumes, filling and emptying dynamics, and systemic hemodynamic parameters during CNP infusion. In addition, we assessed the renal effects of CNP by evaluating RPF, GFR, and intrarenal sodium handling.…”
mentioning
confidence: 99%
“…Previous studies using similar doses and long continuous infusion of ANP and BNP showed increase of HR (up to 20%) and decrease of MAP (up to 6%), as well as being diuretic [37][38][39][40]. In the pilot study using very high pharmacological doses, we also saw an effect on STA but not on radial artery.…”
Section: Discussionsupporting
confidence: 64%
“…The observed decrease in plasma BNP in response to posture‐induced changes in central volume could even be a compensating mechanism to prevent orthostatic hypotension. Infusion of low doses of BNP into normal subjects does not reduce peripheral vascular resistance or CO, while it decreases stroke volume [20,22]. This suggests that BNP does not primarily affect the arterial vascular bed, but rather reduces preload, possibly by lowering venous return.…”
Section: Central Hemodynamic Effects Of Bnpmentioning
confidence: 99%
“…Normal plasma levels of BNP vary from 4 to 35 pg/mL (or 1.2-10 pmol/L) [17][18][19][20][21][22][23][24][25][26][27] (for review see [28]). These levels rise with age and are higher in females than in males [17].…”
Section: Introductionmentioning
confidence: 99%